ac Stark effect in the electronic continuum and its impact on the photoionization of atoms by coherent intense short high-frequency laser pulses - Demekhin, Philipp V.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2013)
We investigate the photoionization of an atom by a high-frequency strong coherent laser pulse, where the energy of a single photon is sufficient to ionize the system. Ab initio theory exemplified by numerical calculations of the photoionization of the hydrogen atom illustrates that the laser pulse induces a time-dependent ac (or dynamic) Stark shift of the binding energy of the system due to interaction with the electronic continuum. The energy shift follows the pulse envelope. Because of this shift, the energy of the emitted photoelectron also follows the intensity envelope of a short laser pulse. This results in a strong dynamic interference of the photoelectrons of the same kinetic energy emitted at different times, when the pulse arrives and expires, respectively. The dynamic interference leads to interesting modifications of the photoionization process and results in a multiple peak structure in the photoelectron spectrum. The present work provides a detailed theoretical and numerical study of the results reported in Demekhin and Cederbaum [Phys. Rev. Lett. 108, 253001 (2012)]. The working equations are derived explicitly and an extended analysis of the theory is provided. Additional results are presented. In particular, we demonstrate that the dynamic interference can be controlled by the intensity, duration, and shape of the pulse envelope.